The diagnosis and therapy of comorbid anxiety and depression disorders in clinical practice - N. N. Petrova; K. S. Savickaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Objective: to discuss problems of diagnostics and psychopharmacotherapy of associated depressive disorders and anxiety circle disorders.Material and methods. The article is an analysis of a clinical case with the use of clinical and catamnestic method.Results. Diagnostics of Generalized Anxiety Disorder, issues of its comorbidity with other mental disorders including anxiety and depressive disorders are discussed. The principles of panic disorder diagnosis are analyzed. Diagnostic criteria of associated anxiety and depression in ICD-10, DSM-5 and ICD-11 are considered. Modern approaches to the choice of therapeutic tactics in comorbidal anxiety and depression are given. The analysis of the patient’s treatment is carried out with the justification of the choice of drugs. The possibilities of combined therapy of associated anxiety and depression disorders using vortioxetine are demonstrated. Achievement of qualitative remission of mental disorder without residual symptomatology and full restoration of social functioning of the patient with associated depressive and anxious disorders is shown.Conclusion. The clinical case demonstrates a characteristic chronic fluctuating course of GTR both in combination with different depths of depression and with other anxiety disorders (panic attacks). Diagnostic difficulties and therapeutic possibilities of a patient with double diagnosis: Generalized Anxiety Disorder and Depressive Episode have been analyzed.